The Relevance of Ibn Miskawayh's Ethics Concept to Character Education in Indonesia within the Framework of Strengthening Character Education - Nazri Adlani Harahap; Masganti Sitorus; Ahmad Syukri Sitorus (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This study aims to analyze the relevance of Ibn Miskawayh’s concept of morality to character education in Indonesia within the framework of Strengthening Character Education (Penguatan Pendidikan Karakter/PPK). The study employs a qualitative approach using a library research method. Data were obtained from Ibn Miskawayh’s major work, Tahdhīb al-Akhlāq wa Taṭhīr al-A'rāq, as well as relevant books, scholarly articles, and policy documents. The data were analyzed using content analysis through the processes of data reduction, categorization, interpretation, and conclusion drawing. The findings indicate that Ibn Miskawayh’s concept of morality, which emphasizes habituation (taʿwīd), exemplary conduct, self-control, and purification of the soul, has strong relevance to the implementation of PPK. The four principal virtues he proposed al-ḥikmah (wisdom), al-ʿiffah (self-control), al-shajāʿah (courage), and al-ʿadālah (justice) are closely connected to the five core values of PPK: religiosity, nationalism, independence, mutual cooperation, and integrity. This study contributes a conceptual synthesis that positions Ibn Miskawayh’s thought as a philosophical foundation for strengthening character education in Indonesia. Thus, integrating Ibn Miskawayh’s concept of morality with PPK can serve as an alternative approach to developing an educational system that is oriented not only toward academic achievement but also toward cultivating students who possess noble character, integrity, and the capacity to face the challenges of the digital era.